Glottotheory : International Journal of Theoretical Linguistics (De Gruyter (A), 2008)
Glottotheory serves as a platform for a dialogue between quantitative and qualitative linguistics. The main foci of the journal include observations and descriptions of all aspects of language and text phenomena on all levels of linguistic analysis, and applications of methods, models or findings from quantitative linguistics. The journal also addresses methodological problems in measurement and sampling as well as epistemological issues.